Análise de perda e fluorescência em fibras de cristal fotônico com líquidos e polímeros - Ong, Jackson Sen Kiat (2008)
Photonic Crystal Fibers (PCFs) have led to renewed attention to the fiber optics field due to the several unique properties resulting from their microstructured profile. In particular, this profile enables one to insert liquids and polymers into the fiber so that they efficiently interact with light, which can be used for chemical and biological sensing, nonlinear optics, and the development of active photonic devices. Several applications require selectively inserting the sample into the core of a hollow-core PCF, leaving cladding holes unfilled. This dissertation presents two contributions toward the development of core-filled PCFs. Loss mechanisms in liquid-core PCFs are studied and fluorescence from a quantum-dot-doped polymer-core PCF is demonstrated. Loss studies were motivated by the evaluation of the transmission of light at 633 nm in 5-7 cm long water-core PCF samples the tips of which are cleaved at left in air. It was generally found that transmission was less than 5%, while water attenuation alone would lead to ~98% transmission. Liquid evaporation was found to be an important additional loss mechanism and its rate was determined both through microscopy and optical coherence tomography (OCT) in capillary fibers and PCFs filled with deionized water, ethanol and toluene. Although the evaporation rate in ethanol was found to be higher, for all samples a few hundreds of micrometers at the fiber tips are emptied over minutes. A method to prevent evaporation consisting of sealing the fiber tips with a clear UV curable polymer (NOA 73) was successfully tested. Filling a PCF with active elements can lead to optical amplification and laser action. Researchers at NTT recently observed fluorescence at 609nm from CdSe quantum dots in the core of a 1m long PCF. In this dissertation, the fluorescence emission is described from ~2.2 nm PbS quantum dots was observed with a specified emission peak of 890 nm. The quantum dots were suspended in NOA73 and inserted in the core of 7-9 cm long PCFs of with a hollow core diameter of 10.9 5m. The fiber was pumped by a 2.5 mW He-Ne laser or a 679 nm, 390 mW diode laser and its emission was characterized. A maximum fluorescence power of 2.2 5W and a maximum efficiency of 0.03% were achieved. Varying the quantum dot concentration revealed that lower concentrations lead to higher efficiencies.